Long-term potentiation and spatial memory training stimulate the hippocampal expression of RyR2 calcium release channels - Valdés-Undurraga, Ismael; Lobos, Pedro; Sánchez-Robledo, Virginia; Arias-Cavieres, Alejandra; SanMartín, Carol D.; Barrientos, Genaro; More, Jamileth; Muñoz, Pablo; Paula-Lima, Andrea Cristina; Hidalgo, Cecilia; Adasme, Tatiana (Frontiers in Cellular Neuroscience, 2023)
Introduction: Neuronal Ca2+ signals generated through the activation of Ca2+-induced Ca2+ release in response to activity-generated Ca2+ influx play a significant role in hippocampal synaptic plasticity, spatial learning, and memory. We and others have previously reported that diverse stimulation protocols, or different memory-inducing procedures, enhance the expression of endoplasmic reticulum-resident Ca2+ release channels in rat primary hippocampal neuronal cells or hippocampal tissue. Methods and Results: Here, we report that induction of long-term potentiation (LTP) by Theta burst stimulation protocols of the CA3-CA1 hippocampal synapse increased the mRNA and protein levels of type-2 Ryanodine Receptor (RyR2) Ca2+ release channels in rat hippocampal slices. Suppression of RyR channel activity (1 h preincubation with 20 μM ryanodine) abolished both LTP induction and the enhanced expression of these channels; it also promoted an increase in the surface expression of the α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptor subunits GluR1 and GluR2 and caused a moderate but significant reduction of dendritic spine density. In addition, training rats in the Morris water maze induced memory consolidation, which lasted for several days after the end of the training period, accompanied by an increase in the mRNA levels and the protein content of the RyR2 channel isoform. Discussion: We confirm in this work that LTP induction by TBS protocols requires functional RyR channels. We propose that the increments in the protein content of RyR2 Ca2+ release channels, induced by LTP or spatial memory training, play a significant role in hippocampal synaptic plasticity and spatial memory consolidation.